ANALISIS PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN, GROVER, DAN SPRINGATE PADA PERUSAHAAN JASA TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2016-2018 - Diana Gustinya, SE., M.Ak.; Nia Kurniawati (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Analyze the differences between the Altaman model, the Grover model, and the Springate model in predicting financial distress. The data analysis method for testing hypotheses using SPSS software is the Paired Sample T-Test method. With the data source used, namely secondary data in the form of annual financial statements of transportation service companies for the period 2016 to 2018. According to the Altman model from 78 samples of companies in transportation service companies that were sampled in this study, 71 companies were predicted to go bankrupt. Meanwhile, according to the Grover model of the 78 samples of transportation service companies that were sampled in this study, 4 companies were predicted to go bankrupt and 74 other companies were predicted not to go bankrupt. According to the Altman model from 78 samples of transportation service companies sampled in this study, 71 companies were predicted to go bankrupt. Meanwhile, according to the springate model, from 78 samples of transportation service companies, 65 companies are predicted to go bankrupt and 13 other companies are predicted not to go bankrupt. The Altman model is the most suitable prediction model applied to transportation service companies because this model has the highest level of accuracy compared to other predictions, namely 91.0%. While the Grover model has an accuracy rate of 5.1% and the Springate model has an accuracy rate of 83.3%.